Improving Community Administration Service and Population Reporting through SINANAS Development Using Participatory Method - Wirastuti, Ni Made Ary Esta Dewi; Hartawan, I Gusti Agung Komang Dlafari Djuni; Suyadnya, I Made Arsa; Khrisne, Duman Care; Mkwawa, Is-haka; Arya Mertasana , Putu (Universitas Ahmad Dahlan, 2023)
Background: Information technology in community administration service has been developed in helping to raise the efficiency and productivity of the leader of Banjar Dinas works, as well as organizing and utilizing information to support administration and management, policy development and decision-making. Contribution: SINANAS (Administration Information System for Banjar Dinas) has proposed to support the works of “Kepala Lingkungan” in Sempidi for administration service and population reporting. Method: Using interview and participatory approaches, the application was used by training and socialization. The application was developed using Visual Studio Code and Python language programming. Results: The results of this community service are SINANAS reporting page for population data of education and livelihood, religion, ethnicity, race, number of population, family card, Temporary Resident Identity Card (KIPS), Temporary Resident Registration Certificate (STPPTS), Reporting page for religion, ethnicity, race, and population, Reporting page for total population based on single age group and gender Conclusion: Based on the post-questionnaire, “Kepala Lingkungan found that using the SINANAS application, producing annual and monthly administrative reports is easier and quicker than manually creating them in Microsoft Word and Microsoft Excel.